Seismic Performance Evaluation of Reinforced Concrete Frames Using Pushover Analysis - Abhraneel Saha; Aditya Pandey (Marasofi International Media and Publishing (MIMP), 2025)
Seismic performance evaluation of reinforced concrete (RC) frame structures is essential to assess their safety and resilience against earthquake loading. Among nonlinear static procedures, pushover analysis has emerged as a practical and widely accepted method for estimating the seismic capacity of building structures. This study aims to assess the seismic performance of RC moment-resisting frames through pushover analysis based on the capacity curve. A mid-rise RC frame model was developed and analyzed using ETABS software, subjected to gradually increasing lateral static loads until structural failure occurred. The analysis focused on lateral displacement behavior, internal force distribution, and performance level evaluation based on FEMA 356 and ATC-40 criteria. The results indicate that the structure generally performs within Immediate Occupancy (IO) to Life Safety (LS) performance levels depending on the applied lateral load. The formation of plastic hinges was predominantly concentrated in beams and lower-level columns, exhibiting typical ductile behavior. This research confirms the value of pushover analysis as an effective and cost-efficient tool to identify structural weaknesses and inform seismic retrofitting strategies in vulnerable RC frame buildings.